Implementasi Program Jumat Bersih Dalam Pembinaan Karakter Peduli Lingkungan Siswa di SD Madani - Ratih Dwi Setiawati; Firman Robiansyah; Darmawan Darmawan (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
This research purpose is to determine, identify, and describe the 1) process of implementation of the Clean Friday program; 2) the implication of the Clean Friday program on caring character building for the environment at Madani Elementary School. The research uses a kualitative approach with a case study method. Subjects researched were students in grades IV and V. The research location was at Madani Elementary School in Cilegon, Banten. The data collection techniques in this study were participant observation, in-depth interviews, documentation studies, and questionnaires. In this research, it was found that 1) the process of implementing clean Fridays, namely routine cooperation activities, was carried out on Fridays at 13.00 WIB to clean the school environment with an estimated time of 15-30 minutes and accompanied by the teacher; 2) the implication of the Clean Friday program on student character building are seen from the questionnaire filled out by 49 respondents that 94% of students answered correctly and 6% of students answered incorrectly. Therefore, the Clean Friday program can be used as an alternative for the character building of care for the student's environment